Ophthalmic surgeries on post mortem porcine eyes with picosecond ultrashort laser pulses - Körber, Michael; Fellinger, Jakob; Fritsche, Milan; Giese, Andreas; Kostourou, Konstantina; Kopf, Daniel; Kottcke, Manfred; Luciani, Francesco; Schmidbauer, Josef M.; Wenk, Jonathan; Braun, Bernd (Frontiers in Medicine, 2024)
Purpose: This work demonstrates significant advantages in ophthalmic surgeries through the use of picosecond ultrashort laser pulses instead of state-of-the-art nanosecond laser pulses. These ultrashort lasers shall serve as universal tools more effectively combining advantages of high precision, low impact and economic advantages compared to existing instruments. Methods: As samples, we used post-mortem porcine eyes on which we performed the experiments with both picosecond and nanosecond lasers. Performed surgeries were laser iridotomy, (post-) cataract treatment/capsulotomy and selective laser-trabeculoplasty. Pulse widths were between 12 ps and 220 ns with pulse energies between 30 μJ and 10 mJ at 532 nm and 1064 nm. Additionally, we investigated accompanying shock waves, cavitation bubbles, and heat effects during the ablation processes.Results: For all surgeries, significant differences were observed between picosecond and nanosecond pulses: It was possible to scale the pulse energy down to tens of microjoules rather than requiring millijoules, and resulting tissue ablations are much more precise, more deterministic and less frayed. The shock wave and cavitation bubble investigation revealed major differences in pressure between picosecond pulses (0.25 MPa, 50 μJ) and nanosecond pulses (37 MPa, 5 mJ). The heat input during ablation could be lowered by two orders of magnitude. Conclusion: Picosecond ultrashort laser pulses show substantial benefits for several ophthalmic surgeries, with regard to ablation precision, shock wave generation and heat input. They are better than state-of-the-art ophthalmic nanosecond lasers in all aspects tested.